(untitled) (Cadernos de Sociomuseologia, 2023)
The present article deals with the execution of technical collaboration between the Federal Institute of Science and Technology of Rio Grande do Sul and the Federal University of Pelotas, through the development of the project entitled "Management of Reserves: Acting of the course of Conservation and Restoration of the UFPel next to the Public and Private Institutions". Recognizing the importance of the scientific, technological and industrial heritage that constitutes the collections of higher education institutions and trying to delimit the possible actions of Conservation and Restoration in order to contribute to the construction of critical thinking and reflection of the academic community about the social role of collections of educational institutions, the project has in its scope the reorganization and development of a search tool in the form of database of the pieces deposited in the technical reserves of the Museum of Telecommunications and the Course of Conservation and Restoration that will serve as a model for access and socialization of these collections for other institutions. Keywords: University Technical Reserves; Technical Collaboration; Technological Heritage; Scientific Heritage. Industrial Heritage.